The pediatric overhead athlete: what is the real problem? - Sciascia, A.; Kibler, W. B. (Clinical Journal of Sport Medicine, 2006)
Objective: The purposes of this article are to examine shoulder and elbow injuries in pediatric athletes, to evaluate the pathophysiology and pathomechanics that may be associated with the pathoanatomy, and to present suggestions for the prevention of those injuries.